The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021 Annual Modeling and Simulation Conference (ANNSIM) 2021
DOI: 10.23919/annsim52504.2021.9552126
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Dissemination Strategies on Temporal Networks

Abstract: When citing, please refer to the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…gossiping on a scale-free network). On this side, PADS techniques have already demonstrated that they can significantly reduce the amount of time that is required to complete the simulation runs while enabling the simulation of larger network topologies [9,[23][24][25][26].…”
Section: Simulation Of Blockchainsmentioning
confidence: 99%
“…gossiping on a scale-free network). On this side, PADS techniques have already demonstrated that they can significantly reduce the amount of time that is required to complete the simulation runs while enabling the simulation of larger network topologies [9,[23][24][25][26].…”
Section: Simulation Of Blockchainsmentioning
confidence: 99%
“…The Neighbors in the Island will share the information regarding their availability status and current opened state channels capacities and fees for their relay. The messages can then be exchanged using different dissemination strategies [5]. A Neighbor that decides to send a message to a Server S becomes a Client C and seeks to reach a Data Mule M through a T N and through (zero or) some mediators, i.e.…”
Section: Indamul Applicationmentioning
confidence: 99%
“…We consider a smart-village-like scenario where buses and couriers act as Data Mule. The simulations, performed with the LUNES agent-based simulator [5], will be aimed to show the potential delays depending on the presence of islands and mule couriers.…”
Section: Future Workmentioning
confidence: 99%
“…) is an open source discrete event simulator, specifically designed for the modelling and performance evaluation of complex networks and communication protocols. LUNES is implemented on top of ART ÌS/GAIA simulation middleware, which offers the primitives for time management and communication among simulated entities, enabling also a parallel and distributed execution [14].In previous works, some versions of this tool have been employed to model blockchain behaviour, edge computing scenarios or temporal networks and in this work a version of LUNES has been developed for InDaMul [15]. This version of the software combines a part where the mobility of the data mules is handled, a part intended to manage the exchange of messages and, finally, a part responsible for collecting and assembling data during the execution.…”
Section: Lunes (Large Unstructured Network Simulatormentioning
confidence: 99%